Life and Career Skills among Technical and Vocational Education and Training (TVET) Students in Vocational Colleges - Abdullah, Nurhanim Saadah; Sumarwati, Sri; Abd Aziz, Mohd Ismail (Online Journal for TVET Practitioners, 2020)
This research aims to investigate whether life and career skills are being embedded by the education institutions especially in the technical and vocational education since it provides a semi-skilled and skilled workforce to compete in the global labor market. Furthermore, this study focusses on vocational college students because there is little study on the life and career skills being done to this institution. Besides, this study also will compare the life and career skills between male and female students. A quantitative approach using a cross-sectional survey design was employed to determine the information of life and career skills from respondents. An instrument consist of 80 items was developed by the researcher by adapting and adopting questions related to life and career skills. Based on the pilot study, the findings show that the value for Cronbach's Alpha for five elements of life and career skills is more than 0.7. This is indicated the instrument to be considered as a reliable questionnaire. The total sample in this study is 275 Technical and Vocational Education and Training (TVET) students in Vocational Colleges in Johor, were selected using random sampling. The actual study data were analyzed using IBM Statistical Package for The Social Science (SPSS) version 21. The data were analyzed using descriptive and inferential statistics using a t-test. This result in this research shows that the Flexibility and Adaptability skills at the highest level possessed by the students in vocational colleges in Johor. The finding this study also showed that there were statistical differences between male and female students in vocational colleges on Flexibility and Adaptability skills, Social and Cross-cultural skills, Productivity and Accountability skills, and Responsibility and Leadership skills. However, there was no significant difference between students' gender on Initiative and Self-direction skills. The mean score of male students was higher compared to female students in all five elements of life and career skills. Finally, some suggestions for future studies were discussed to help future researchers to find gaps in the field of 21st-century skills.